The effectiveness of oral health education conducted at a rural community market setting (2013)
Background: The workplace is one of the avenues for educating the public about their oral health in developing countries; particularly in rural communities where the workplace plays a major role in communal living. It is therefore necessary to find out if the market is appropriate for achieving the set aim of improving oral health awareness among the populace in rural communities. Aim and Objectives: The aim of this study was to determine the effectiveness of oral health education conducted in a market in a rural community by comparing the oral health practices of market women involved in the oral health education programme to those not involved in the programme. Design: A prospective study. Setting: A rural community in South-western Nigeria. Subjects & Methods: A prospective study was conducted among market women in Igboora, a rural community in Southwestern Nigeria. The intervention was oral health education differentiating between the intervention group and the control group. Structured interviewer administered questionnaires were used to obtain information from the participants on their oral hygiene measures, fluoride use, dental attendance and the demographics of the participants. Data collected was analyzed using SPSS and p-value set at <0.05. Results: Two hundred market women participated in the study with a mean age of 45.2 ± 17 years. The interventional group was made up of 106 market women while the control group was made up of 94 market women. There were no significant differences in the sociodemographic characteristics of women in both the intervention and control groups. Women in the intervention group engaged in more frequent cleaning of their teeth and tongue than those in the control group (p < 0.001). Market women who had participated in the oral health education subsequently visited the dentist more often than those in the control group (p = 0.010). Conclusion: The study showed that oral health education conducted at a market was effective in improving some oral health practices of participants. It is recommended that oral health practices be extended to major markets in our communities